Revolutionizing the Drive: Exploring Consumer Perceptions of Innovative Automatic Transmission Technologies in India’s Automobile Sector - Fredrick, Tony; Jayaraman, Yuvaraj (Journal of Global Economy, Business and Finance, 2025)
The automobile sector today is one of the important sectors of the country contributing the majority to the economic development of India. The challenges that today's automotive manufacturers face are enormous. Internationalization, the rapid pace of technological progress, and customer demand have all had an impact on how businesses are conducted. Product innovation has been a trademark of the auto industry for the last decades. One of the major innovations of automakers is the development of automatic transmission technologies in a different form which has been successfully adopted by Major players like Maruti Hyundai, Tata and others to lower driving efforts and to experience stress-free driving among consumers. There are majorly five types of automatic transmission technologies available in the Indian market. These are AMT (Automated Manual Transmission ), CVT (Continuously Variable Transmission), IMT (Intelligent Variable Transmission), DCT( Dual clutch transmission), and Torque Converter (TC). The demand for automatic cars is increasing remarkably in the last five years, especially in small passenger car segments. This study is about understanding the consumers' perception of different types of automatic transmission technologies adopted by carmakers.